Gain enrichment of wideband antenna utilized on artificial magnetic conductor surface. (2021) - Sakthisudhan, K.; Amirthalakshmi, T.M.; Sankar Ganesh, S.; Nandhakumar, S.
Abstract: The 3x4 array pattern of Jerusalem cross shaped microstrip patch antenna have designed, fabricated and validated in this paper. It consists of 1 mm thickness of substrate mounted on metal strips which is one side of conductive strip of 31.25 × 22.9 mm 2 and another side of conductive strip of 37.25x 28.9 mm 2 for ground plane. The fabricated design has provided the return loss of 27.106 dB at 3.884 GHz and Fractional Bandwidth (FBW) of 23.68%. Therefore, these fabrication results have validated with vector network analyser.